Reviews in Computational Chemistry (Wiley VCH, 2006)
This respected series is designed to help the chemistry community keep current with the many new developments in computational techniques. Volume 6 examines quantum chemistry of solvated molecules, molecular mechanics of inorganics and organometallics, modeling of polymers, technology of massively parallel computing, and productivity of molecular modeling software. A guide to force field parameters and a compendium of computational chemistry software are included to provide background information